PHP and MySQL for Dummies, Second Edition - Valade, Janet (Wiley Publishing, 2011)
Shows Web developers how to use two popular open source technologies, the PHP scripting language and MySQL database, to build Web database applications This updated edition covers changes in PHP 5 and the latest version of MySQL, including programming techniques for the new PHP default setting, methods for handling MySQL security problems, and extended information about Apache Web Server and Mac OS X versions of PHP and MySQL Explains how to install Windows, Linux, and Mac OS X versions of PHP and MySQL Includes two complete sample applications: an online catalog and a members-only Web site Features a companion Web site with code examples from the book and links to the author's successful site Kevin Beaver has more than fifteen years of experience in security and information technology, specializing in security assessments and incident response Features a companion Web site with links to various utilities discussed throughout the book and practical security checklists